MODELING AND FORECASTING OF TEA PRODUCTION IN INDIA - H.K.Niranjan; B. Kumari; Y. S. Raghav; P. Mishra; A.M. G. Al Khatib; M.Abotaleb; Supriya (Journal of Animal and Plant Sciences, 2022)
There are many measures of the importance of a crop to the economy, including its area, output, and yield increase. The current study will look at the growth rates of tea acreage, output, and yield in India using training data from 1918 to 2015 and testing data from 2016 to 2018. Using the data acquired, the ARIMA model and State Space Models were used to anticipate the area, production, and yield of tea from 2021 to 2027. According to the data, tea production in India is expected to reach 607 thousand hectares by2027, reflecting a 3.93 percent increase between 2021 and 2027. India's tea production is expected to reach 1486 thousand tonnes in2027, reflecting a 10.56 percent increase between 2021 and 2027. However, the tea production in India is expected to reach 2449 kg/hectare between 2021 and2027, reflecting a 4.12% increase over the preceding five-year period. The most essential tools for increasing tea production were area expansion and yield increase. As a result, the emphasis should be on expanding the area by exploiting available land and boosting productivity through technological advancements, varietal research, and the enhancement of agricultural advisory services across India.
Keywords: Growth rate; Trend; Area; ProductionTea; India; ARIMA; Forecast; State Space Models